(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study attempts to examine the factors that influence the students to prefer particular higher education institution for their study. This study further examines the level of perceived service quality by the students towards college teachers in aided colleges. To conduct the study on the service quality of college teachers working in aided colleges in Kanyakumari district, the relevant data were collected from both the primary and the secondary data. The primary data was collected using the questionnaire from the respondents. To ease the data collection from the college students, the questionnaire was prepared. The data was collected from the students who are studying in aided colleges in Kanyakumari district. The secondary data was collected from books, articles, newspapers and previous research papers. The total numbers of final year students in Aided Colleges is 300. 300 final year students have been taken as sample respondents. Thus 300 from Aided colleges were selected by random sampling method. Teaching is considered one of the noble professions and teachers are the walls on which the students have to draw and it is imminent that the teachers should have a strong mind and body to engrave the future challenging generation.